PILOT PLANT KOMBINASI BIOFILTRASI DENGAN ULTRAFILTRASI UNTUK PENYEDIAAN AIR MINUM - Widayat, Wahyu (Jurnal Air Indonesia, 2015)
In big cities of Indonesia using river water as raw water PAM (drinking water company). The concentration of organic matter and ammonia in the raw water PAM is increasing due to industrial and domestic waste pollution. Biofiltration combination with ultrafiltration process is use as one alternative to reduce concentration of organic matter, ammonia, iron, manganese and turbidity in raw water. In this treatment, biofilter reactor is use with plastic of Honeycomb tube type as media combined with ultrafiltration. Operational condition of treatment is variation of HRT (Hydraulyc Retention Time) between 1–4 hours and air supply between 0–30 l/min. The selected operational condition of treatment found at HRT of 2 hours and air supply of 20 l/min, with removal efficiency of concentration of organic, ammonia,iron, manganese, and turbidity are 68 %,65 %, 68 %, 67 %, and 72 % respectively. Keywords: Biofiltration, ultrafiltration, honeycomb tube, removal efficiency, drinking water.